ASSESSMENT OF EMISSION AND PERFORMANCE OF COMPRESSION IGNITION ENGINE FUELED WITH RUBBER SEED OIL AT DIFFERENTINJECTION TIMING - Manjunatha M.C.; D.K. Ramesha; Honnegowda (International Journal of Innovations in Engineering Research and Technology, 2021)
Energy is an indispensable factor for human to preserve economicgrowth and maintain standard of living. As the fossil fuels are depleting day by day, there is a need to find out an alternative fuel to fulfill the energy demand of the world. Biodiesel is one of the best available resources that have cometo the forefront recently.Engine performanceimprovementandexhaustemission’sreductionarethetwomostimportantissues to developamoreefficient enginewithfewer environmentsa impact.Foradieselengine,injection timingis oneofthemajorparameters thataffecttheengineperformanceandmissions.Inthispaper, studiesare focused oncharacterizinginfluence ofinjectiontimingonengineperformanceandexhaustemissions.Experiments were conducted on a 4-stroke, water cooled, direct injection, compression engine with 20% blend of rubber seed oilmethyl ester (RSOME)and Diesel. Performance and emission parameters were studied at different injection timings (i.e. 230bTDC, 270bTDC, 300bTDC and 330bTDC).